BRAIN-PENETRATING AMINOPEPTIDASE A INHIBITORS FOR NEW TREATMENT OF HYPERTENSION AND HEART FAILURE. (April 2021) - Llorens-Cortes, Catherine; Hmazzou, Reda; Boitard, Solene; Marc, Yannick; Keck, Mathilde; Balavoine, Fabrice; Roques, Bernard
Abstract : Objective: Brain renin-angiotensin system (RAS) hyperactivity is involved in the pathophysiology of hypertension and heart failure (HF). Angiotensin III/(AngIII), one of the main effector peptides of the brain RAS, exerts tonic stimulatory control over blood pressure/(BP) in hypertensive rats and plays a pivotal role in sympathetic hyperactivity and left ventricular/(LV) dysfunction in rats post-myocardial infarction/(MI). Thus, aminopeptidase A/(APA), the enzyme generating brain AngIII represents a potential therapeutic target for the treatment of these pathologies. Our aim was to evaluate the mode of action of firibastat, a brain-penetrating prodrug of the APA inhibitor, EC33, to reduce BP in hypertensive rats and prevent LV dysfunction in mice post-MI. Design and method: Firibastat and MLN4760, an angiotensin-converting enzyme2/(ACE2) inhibitor were administered by central route in hypertensive DOCA-salt rats and mean arterial BP (MABP) was recorded following insertion of a catheter into the femoral artery. Brain APA and ACE2 activities were measured 30 min post-treatment. Two days post-MI induced by the left anterior descending artery ligation, mice were randomized to receive during 4–8 weeks oral treatment with vehicle, firibastat (150 mg/kg) or the ACE inhibitor, enalapril (1 mg/kg). Cardiac function was evaluated by echocardiography Results: 1-Firibastat, when given centrally in hypertensive rats, is immediately cleaved by brain reductases, generating EC33 which inhibits brain APA activity, blocks brain AngIII formation and decreases BP. At the same time, firibastat treatment increases the activity of brain ACE2, majoring the conversion of AngII to Ang1-7, which by acting on the Mas-receptor, participate to the firibastat-induced BP decrease. 2-Chronic firibastat treatment in mice post-MI normalizes brain APA activity (normalizing brain RAS activity) and prevents sympathetic hyperactivity. It reduced LV end-diastolic pressure, LV end-systolic diameter and volume, and increased LV ejection fraction. It decreased the expression of HF and fibrosis biomarkers. Firibastat treatment prevents cardiac dysfunction and attenuates cardiac hypertrophy and fibrosis. Conclusions: Following these data, firibastat was selected for clinical development. Phase IIa/IIb clinical trials provided pharmacological proof-of-principle of firibastat efficacy for decreasing BP in hypertensive patients. The ongoing phase II study/QUORUM will determine if firibastat treatment may constitute a new therapeutic approach for preventing HF post-MI.